ChemInform Abstract: Hollow Carbon Spheres, Synthesis and Applications ‐ A Review. Issue 42 (28th September 2016) - Li, Sijin; Pasc, Andreea; Fierro, Vanessa; Celzard, Alain
Abstract: Review: 151 refs.